Naheun Lee: capstone - Lee, Naheun, artist (Colorado State University. Libraries, 2023)
The artist's statement: I am a graphic designer who brings creativity to art. My art is made digitally with Adobe programs and drawings. I grew up watching a lot of cartoons and animation which got me into graphic art. My work is based on two dimensional characters and objects which influenced me to work with cartoon types of characters. I do a lot of sketching in a creating process because that is where all the good ideas come from. Even though I am not confident about some ideas I still sketch it because it has possibilities to come out with something great. That is fun about art when failure can result in success. After I am done with my sketches I use illustrator to create my objects and use photoshop to add finishing touches to my work. Art is a tool where I can express and heal myself. The more I release my energy to something I am passionate about, it becomes a thing I want to pursue in my career. Art sets a navigation and helps me sail my way to the creative process. My work represents myself and creates identity. It shows what kind of character I am and how I speak to others. It is a great way I can communicate with the audience what I am voice in my art. My goal is to become an artist where I can send powerful messages to people like how cartoons give lessons that we don't realize when we are young.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design